Musculoskeletal multibody simulations for the optimal tribological design of human prostheses: the case of the ankle joint. Issue 1 (January 2020) - Ruggiero, A; D'Amato, R; Ungureanu, N
Abstract: A thorough determination of the loading of the ankle joint is useful both for the optimal design of prostheses and for the preclinical testing in terms of tribological performances. In vivo measurements of joint forces are usually not easy in the in-vivo settings, then non-invasive in-silico methods should be considered. Nowadays resultant joint loads can be reliably estimated by using musculoskeletal modelling in an inverse dynamic approach, starting by motion data obtained in gait analysis laboratories for several human activities. The main goal of this study was to provide a set of dynamical loading curves obtained by the AnyBody Modelling SystemTM (AMS) computer software starting from ground reaction forces and kinematic data obtained by Vaughan et al. in the case of human normal gait. The model accounts for 70 Hill modelled muscles and the muscular recruitment strategy was choose as polynomial criteria. The results are presented in terms of Antero Posterior, Proximo Distal, Medio Lateral Forces and Ankle Eversion, Plantar Flexion, Axial moments, discussing their role on the synovial lubrication phenomena effect in the Total Ankle Arthroplasty (TAR) for the optimal prostheses structural and tribological design.